2023
DOI: 10.3390/toxins15040253
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mitochondrial Fission Alleviates Zearalenone-Induced Mitochondria-Associated Endoplasmic Reticulum Membrane Dysfunction in Piglet Sertoli Cells

Abstract: This study aimed to investigate the effects of zearalenone (ZEA) on piglet Sertoli cell (SC)-mitochondria-associated endoplasmic reticulum (ER) membranes (MAMs) based on mitochondrial fission, and to explore the molecular mechanism of ZEA-induced cell damage. After the SCs were exposed to the ZEA, the cell viability decreased, the Ca2+ levels increased, and the MAM showed structural damage. Moreover, glucose-regulated protein 75 (Grp75) and mitochondrial Rho-GTPase 1 (Miro1) were upregulated at the mRNA and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, both IHC and Western blot analyses showed a decreased expression of BTB junction proteins in ZEA-treated testicular tissue, which was consistent with previous reports in mice [ 22 , 23 ]. In addition, considerable studies have also indicated that ZEA treatment, when in vitro, can hinder the survival of SCs and destroy the structure of the BTB through different signaling pathways to cause testicular toxicity [ 13 , 24 , 45 , 46 ]. In mammalian testes, SCs are the major somatic cells of the seminiferous tubules and play crucial roles in spermatogenesis and the regulation of testicular function [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, both IHC and Western blot analyses showed a decreased expression of BTB junction proteins in ZEA-treated testicular tissue, which was consistent with previous reports in mice [ 22 , 23 ]. In addition, considerable studies have also indicated that ZEA treatment, when in vitro, can hinder the survival of SCs and destroy the structure of the BTB through different signaling pathways to cause testicular toxicity [ 13 , 24 , 45 , 46 ]. In mammalian testes, SCs are the major somatic cells of the seminiferous tubules and play crucial roles in spermatogenesis and the regulation of testicular function [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such effects include reductions in mitochondrial membrane potential, along with the liberation of Cyt C and apoptosis-inducing factor (AIF) [ 35 ]. Mfn2 is primarily found in the outer mitochondrial membrane (OMM) and plays a vital role in the establishment and maintenance of MAM structures [ 13 ]. Localizing IFN2 through the ER has been found to induce mitochondrial fission via direct binding to Drp1 and the promotion of Drp1 oligomerization [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the tumor suppressor inhibits the anti-apoptotic factor Bcl-2 in response to DNA damage [ 41 ]. There is evidence from previous studies conducted within our research group suggesting that ZEA has the potential to cause damage to piglet SCs through the mitochondrial fission pathway, while the ER can regulate mitochondria through MAMs [ 13 , 14 ]. This study is based on the previous foundation of in-depth research; according to our WB and qRT-PCR results, in the Z + D group, there was a significant increase in the gene and protein expression levels of Bid , P53 , and Caspase -9.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations